Can they do it? A comparison of teacher candidates' beliefs and preschoolers' actual skills with digital technology and media. (February 2019) - Mourlam, Daniel James; Strouse, Gabrielle A.; Newland, Lisa A.; Lin, Haoyu
Abstract: As digital technologies and media (DTM) are integrated into every facet of our lives, the knowledge and skills children bring to school is changing. It is unclear whether teacher candidates' beliefs about children's skills have kept pace with this change. To explore this issue, 43 children, ages 3–5, and 180 teacher candidates at a medium-sized Midwest research university were recruited. Teacher candidates' beliefs about preschoolers' DTM skills were compared with preschoolers' observed skills following an assessment protocol using an iPad. Findings indicated most preschoolers could complete 9 of the 12 iPad tasks without assistance, whereas teacher candidates frequently assumed that children would need assistance. Teacher candidates mis-estimated preschoolers' skills on 50% of iPad tasks. Findings confirmed that preschoolers can complete multiple tasks using DTM, which could be harnessed by teachers when creating developmentally appropriate learning experiences. The mismatch between teacher candidates' beliefs and children's skills suggests an area for improvement in teacher preparation programs and could be an indication that negative reports in popular media are more influential in shaping teacher candidates' beliefs than knowledge of children's actual DTM skills. Highlights: Observed preschooler iPad skills were compared with teacher candidate assumptions. Preschoolers could complete 9 of the 12 iPad tasks without assistance. Teacher candidates both over- and under-estimated preschooler skills on iPad tasks. Teacher candidates often assumed children would need help; they infrequently did. Findings have implications for teacher preparation and curriculum development.